Evaluation of Christian Religious Education (CRE) Learning Through a Contextual Approach: A Review of the Implementation of CTL at SMTK Gloria Sentani - Roragabar, Yeni Irawati; Irianto, Irianto; Abram, Voneka (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The objective of this research is to evaluate the existence of the core elements of the Contextual Teaching Learning (CTL) method implemented at SMTK Gloria Sentani, along with the impact felt by students if it is not applied inclusively and holistically. The method used in this research is a qualitative descriptive method with a thematic approach. To validate the data, the researcher applied data triangulation sourced from interviews, observations, and document reviews. In analyzing the data, the researcher applied the Miles and Huberman method, which involves data collection, data reduction, data presentation, and analysis. The analysis focuses on the existence and absence of the 5 core elements in the CTL method, which include relating, experiencing, applying, cooperating, and transferring. The results obtained from this research indicate that 3 elements—experiencing, applying, and transferring—are not included, whereas relating and cooperating are included. The impact felt when the CTL elements are not applied holistically is that students do not think creatively and innovatively, do not think critically, and learning outcomes tend not to be achieved. The t fundamental reason for not implementing the CTL method inclusively and holistically is the factor of readiness to learn and students’ background.